A new species of fiddler crab from the Ogasawara (Bonin) Islands, Japan, separated from the widely-distributed sister species Uca (Paraleptuca) crassipes (White, 1847) (Crustacea: Decapoda: Brachyura: Ocypodidae) - Shih, Hsi-Te; Komai, Tomoyuki; Liu, Min-Yun (Zootaxa, 2013)
A new species of fiddler crab (Brachyura: Ocypodidae), Uca boninensis sp. nov., is described from the Ogasawara (Bonin) Islands, Japan. The new species has previously been identified with the widely distributed U. crassipes (White, 1847), from which it differs by having a slightly differently shaped carapace, and relatively stouter male first gonopods (G1). The recognition of the new species is also supported by differences in the mitochondrial cytochrome oxidase I (COI) and control region (CR) genes. U. boninensis sp. nov., appears to be endemic to the Ogasawara Islands, and as the only known population is small, urgent conservation measures are needed for its protection. Our study brings the total number of the Japanese fiddler crab species to 12.